2016
DOI: 10.1111/inr.12270
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a Global Social Network: a quasi‐experimental study

Abstract: In an era where many policy solutions are being debated and initiated at the global level, action learning leadership development that utilizes new technology follow-up appears to show significant impact and is worthy of wider application. The approach warrants further inquiry and testing as to its longer term effects on nursing's influence on policy formulation and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…provides a useful starting point to see how progress can be measured. By using this mapping and by either creating communities of scholarship or through twinning aimed at developing capacity in countries that are either minimally or not yet contributing to scholarship in the field, more inclusive global partnerships are possible (Benton & Ferguson ). Indeed, Benton & Ferguson () identified that the creation and sustainability of global networks are not only relatively easy but can be maintained with minimal e‐based communication.…”
Section: Discussionmentioning
confidence: 99%
“…provides a useful starting point to see how progress can be measured. By using this mapping and by either creating communities of scholarship or through twinning aimed at developing capacity in countries that are either minimally or not yet contributing to scholarship in the field, more inclusive global partnerships are possible (Benton & Ferguson ). Indeed, Benton & Ferguson () identified that the creation and sustainability of global networks are not only relatively easy but can be maintained with minimal e‐based communication.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a study of the social networks of nurse leaders ( 16 ) it was identified that factors associated with the establishment of peer to peer connections was related to geographic proximity, language and participation in professional associations. In a subsequent study, the same authors ( 17 ) identified that technology can be used to maintain links between participants of such networks. Furthermore, although not ideal, the advancement of technology based translating services may help alleviate or even eliminate some of the historical barriers that authors who speak different languages have faced.…”
Section: Discussionmentioning
confidence: 99%
“…a study of the social networks of nurse leaders (16) it was identified that factors associated with the establishment of peer to peer connections was related to geographic proximity, language and participation in professional associations. In a subsequent study, the same authors (17) identified that technology can be used to maintain links between participants of such networks. Turning to Figure 4, and more specifically, Figure 5, there is already a wealth of scholarship that focuses on priority topics that will support PAHO in pursuing a wide range of strategic goals.…”
Section: Methodsmentioning
confidence: 98%